2017
DOI: 10.11648/j.ajim.20170506.12
|View full text |Cite
|
Sign up to set email alerts
|

Anti-diabetic Drugs Utilization in Type 2 Diabetic Patients in AL-Nasiriya Governorate / Iraq

Abstract: To study the utilization pattern of anti-diabetic drugs in type 2 diabetic patients and to evaluate the association of diabetes with demographic details and it's metabolic control. The study was carried out on 100 type 2 diabetic patients who visited AL-Nasiriya center for diabetes and endocrinology. Demographic details and complete prescriptions drugs, FBS (fasting blood sugar), HbA1c and BMI (body mass index) were recorded. A total of 100 type 2 diabetic patients, 27(27%) were males and 73(73%) were females.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(17 reference statements)
0
0
0
Order By: Relevance
“…Most of the patients were female in the present study and this was in consistent with other study. 13 Majority of the patients were illiterate and unemployed in the present study and similar findings were also reported by other reports. 14,15 These findings suggest that individuals with unemployement and less education are two to four times more likely to develop diabetes mellitus and more likely to be affected by the diabetes complications.…”
Section: Discussionsupporting
confidence: 92%
“…Most of the patients were female in the present study and this was in consistent with other study. 13 Majority of the patients were illiterate and unemployed in the present study and similar findings were also reported by other reports. 14,15 These findings suggest that individuals with unemployement and less education are two to four times more likely to develop diabetes mellitus and more likely to be affected by the diabetes complications.…”
Section: Discussionsupporting
confidence: 92%